Probability Based Evaluation of Vehicular Bridge Load using Weigh-in-Motion Data - Nugraha, Widi; Sidi, Indra Djati (ITB Journal Publisher, LPPM ITB, 2016)
Load and Resistance Factored Design (LRFD) method for designing bridge in Indonesia have been implemented for more than 25 years. LRFD method treating loads and strengths variables as random variables with specific safety factors for different loads and strengths variables type. The nominal loads, load factors, reduction factors, and other criteria for bridge design code can be determined to meet the reliability criteria. Statistical data of weigh-in-motion (WIM) vehicular loads measurement in Northern Java highway, Cikampek - Pamanukan, West Java (2011), used in as statistical loads variable. A 25 m simple span bridge with reinforced concrete T-girder is used as a model for structural analysis due to WIM measured and nominal vehicular load based on RSNI T-02-2005, with applied bending moment of girder as the output. The distribution fitting result of applied bending moment due to WIM measured vehicular loads is lognormal. The maximum bending moment due to RSNI T-02-2005 nominal vehicular load is 842.45 kN-m and has probability of exceedance of 5x10-5. It can be concluded, for this study, that the bridge designed using RSNI T-02-2005 is safely designed, since it has reliability index, Î² of 5.02, higher than target reliability, Î² ranging from 3.50 or 3.72.